Relationship between Life Events and the Onset of Psychiatric Disorders in Childhood and Adolescence (Community Based Medical Journal, 2025)
The prevalence of psychiatric problems among children and adolescents is rising in Bangladesh. Children with acute and chronic pediatric diseases have a higher likelihood of developing psychiatric problems, as their physical health challenges can lead to emotional and psychological stress, affecting their overall well-being. Our study aims to explore the relationship between life events and the onset of psychiatric disorders in children and adolescents. This observational study was conducted in the Department of Psychiatry of Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January 2022 and February 2023. A total of 110 patients of both sexes were included in the study. The mean age of patients was 10±3.32 years. Among them, 60% were found to have emotional disorders and the life events and psychiatric disorders show that a majority life events of parent financial crisis with higher rates of (22.73%) emotional disorders. Our study indicates the relation between life events and psychiatric conditions among the paediatric population.  CBMJ 2025 January: Vol. 14 No. 01 P: 70-75